Problematic Dilemma of The Limitation of Granting Remission for Corruption Prisoners - Maroni Maroni; Nenny Dwi Ariani (Universitas Lampung, 2018)
Corruption is an extraordinary crime, so the law enforcement for corruption cases must also be done extraordinarily. Therefore, the corruption prisoners or corruptors should be differentiated by their pattern of guidance in Penitentiary. The difference in the process of fostering in Penitentiary is in the form of limitation of granting remission for corruptors. The existence of such restrictive policy poses a problem dilemma to the guidance of current corruption prisoners based on Penitentiary System. This is because the penitentiary system essentially sees the crime of